Dietary supplementation with New Zealand blackcurrant extract enhances fat oxidation during submaximal exercise in the heat. Issue 10 (October 2020) - Hiles, Ania M.; Flood, Tessa R.; Lee, Ben J.; Wheeler, Lucy E.V.; Costello, Rianne; Walker, Ella F.; Ashdown, Kimberly M.; Kuennen, Matthew R.; Willems, Mark E.T.
Abstract: Objectives: This study investigated the effect of 7 days' supplementation with New Zealand blackcurrant extract on thermoregulation and substrate metabolism during running in the heat. Design: Randomized, double-blind, cross-over study. Methods: Twelve men and six women (mean ± SD: Age 27 ± 6 years, height 1.76 ± 0.10 m, mass 74 ± 12 kg, V̇ O2max 53.4 ± 7.0 mL kg −1 min −1 ) completed one assessment of maximal aerobic capacity and one familiarisation trial (18 °C, 40% relative humidity, RH), before ingesting 2 × 300 mg day −1 capsules of CurraNZ™ (each containing 105 mg anthocyanin) or a visually matched placebo (2 × 300 mg microcrystalline cellulose M102) for 7 days (washout 14 days). On day 7 of each supplementation period, participants completed 60 min of fasted running at 65% V̇ O2max in hot ambient conditions (34 °C and 40% relative humidity). Results: Carbohydrate oxidation was decreased in the NZBC trial [by 0.24 g min −1 (95% CI: 0.21–0.27 g min -1 )] compared to placebo ( p = 0.014, d = 0.46), and fat oxidation was increased in the NZBC trial [by 0.12 g min −1 (95% CI: 0.10 to 0.15 g min −1 )], compared to placebo ( p = 0.008, d = 0.57). NZBC did not influence heart rate ( p = 0.963), rectal temperature ( p = 0.380), skin temperature ( p = 0.955), body temperature ( p = 0.214) or physiological strain index ( p = 0.705) during exercise. Conclusions: Seven-days intake of 600 mg NZBC extract increased fat oxidation without influencing cardiorespiratory or thermoregulatory variables during prolonged moderate intensity running in hot conditions.